Technology of lager and dark beers with chicory roots - Bulii, Yurii; Mukoid, Roman; Parkhomenko, Anastasia; Kuts, Anatoly (My University, 2024)
Chicory root (Cichorium intybus L.) contains valuable components such as inulin, inulides, bitter substances, pectin, and fibers and is a promising non-traditional raw materia The technology for light beer production was proposed, according to which light malt and dried crushed chicory roots taken in the amount of 4% of malt are used as raw materials, and at the stage of mashing the enzyme preparation inulinase with activity of 14 units/g was introduced into the mixture. For the hydrolysis of inulin at the mashing stage, an inulase pause was provided at a temperature of 55–56 °C for 20–30 minutes. The method allows increasing the content of reducing substances in the wort by 1.6%, the apparent and actual fermentation degree by 3.9%, the content of alcohol and carbon dioxide in the beer by 3.2 and 10%, respectively. The finished beer had increased foam resistance and higher foam height, while the introduction of chicory did not impart excessive and extraneous bitterness. The innovative technology of dark beer provides mixing of aqueous extract of roasted chicory with malt wort cooled to the temperature of 85–90 °С. It was found that the optimal mode of the extraction process was the temperature 85–90 °С, hydromodule 1:6, and duration 90 min. Beer with chicory content of 3% was the best in terms of physical, chemical, and sensory properties. The improved method allows to increase the content of reducing substances in wort by 1.5%, apparent and actual fermentation degree by 2.2 and 3%, respectively, to increase the content of alcohol in beer by 2.3%, and carbon dioxide by 3.2%. It was proved that partial replacement of malt by chicory allows to reduce consumption of bitter hops for light beers by 20% (from 14.8 to 12.0 g/dal) and for dark beers by 10% (from 10.3 to 9.3 g/dal).

Корінь цикорію (Cichorium intybus L.) містить такі цінні компоненти, як інулін, інуліди, гіркі речовини, пектин, клітковину і є перспективною нетрадиційною сировиною. Запропоновано технологію виробництва світлого пива, згідно з якою в якості сировини використовують світлий солод і висушені подрібнені корені цикорію, взяті в кількості 4% солоду, а на стадії затирання ферментний препарат інуліназу з активністю 14 од. в суміш вводили г. Для гідролізу інуліну на стадії затирання передбачали інулазну паузу при температурі 55–56 °С протягом 20–30 хв. Спосіб дозволяє підвищити вміст редукуючих речовин у суслі на 1,6%, уявну і фактичну ступінь бродіння на 3,9%, вміст спирту і вуглекислого газу в пиві відповідно на 3,2 і 10%. Готове пиво мало підвищену піностійкість і висоту піни, а введення цикорію не додавало надмірної і сторонньої гіркоти. Інноваційна технологія темного пива передбачає змішування водного екстракту смаженого цикорію з охолодженим до температури 85–90 °C солодовим суслом. Встановлено, що оптимальним режимом процесу екстракції є температура 85–90 °С, гідромодуль 1:6 і тривалість 90 хв. Найкраще за фізико-хімічними та сенсорними властивостями було пиво з вмістом цикорію 3%. Удосконалений спосіб дозволяє підвищити вміст редукуючих речовин у суслі на 1,5%, уявну і фактичну ступінь бродіння відповідно на 2,2 і 3%, збільшити вміст спирту в пиві на 2,3%, вуглекислого газу на 3,2%. Доведено, що часткова заміна солоду цикорієм дозволяє зменшити споживання гіркого хмелю для світлого пива на 20% (з 14,8 до 12,0 г/дал) і для темного пива на 10% (з 10,3 до 9,3 г/дал).
Keywords: кафедра біотехнології продуктів бродіння і виноробства; пиво; коріння цикорію; cусло; інулін; beer; сhicory roots; mash; wort; inulin